ATTITUDES TOWARD TEACHERS, MOTIVATION AND LEARNING ACHIEVEMENT: The case of Indonesian EFL students - Susandi, Ni Kadek Ary; Khaerudin, Teguh (Linguistika: Buletin Ilmiah Program Magister Linguistik Universitas Udayana, 2015)
This study explores the correlation of learners’ attitude towards their English teachers and their motivation and achievement in English class. Two questionnaires on attitude and motivation used in this study were adapted from the Attitude Motivation Test Battery (AMTB) developed by Gardner (1985). These questionnaires were then developed using web-based survey and distributed online to 82 Indonesian students. The quantification of data shows that attitude and motivation are moderately correlated at a value of r = 0.569, p < 0.01, whilst the correlation value between motivation and students’ final score is at r = 0.30, p <0.01. The findings demonstrate a predictive utility of students’ attitudes toward teachers to learning motivation and motivation to learning achievement.
Keywords: language classroom, attitude, motivation, effective learning